2012
DOI: 10.1002/app.37895
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic polycarbonate‐based polyurethane elastomers and nanocomposites. II. Mechanical, thermal, and gas transport properties

Abstract: Thermal, thermomechanical, tensile and gas transport properties of aliphatic polycarbonate-based polyurethanes (PC-PUs) and their nanocomposites with bentonite for organic systems were studied. Hard segments are formed from hexamethylene diisocyanate and butane-1,4-diol. All PC-PUs and their nanocomposites feature high degree of the phase separation. Three phase transitions were detected by temperature-modulated differential scanning calorimetry (TMDSC) and dynamic mechanical thermal analysis. TMDSC revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 30 publications
(81 reference statements)
1
60
0
Order By: Relevance
“…That can be directly related to ascorbic acid behaving as an inactive filler in this PUR system. Noted glass transitions were between -28 and -35°C, what can be attributed to the Tg of the soft segments dHEBA [39,40]. Studies, performed by Hassan et al, reported Tg of different polyester soft segments (made of poly(e-caprolactone), PCL) at -33°C.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 94%
See 1 more Smart Citation
“…That can be directly related to ascorbic acid behaving as an inactive filler in this PUR system. Noted glass transitions were between -28 and -35°C, what can be attributed to the Tg of the soft segments dHEBA [39,40]. Studies, performed by Hassan et al, reported Tg of different polyester soft segments (made of poly(e-caprolactone), PCL) at -33°C.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 94%
“…2b) was lower for modified with ascorbic acid polyurethane samples in comparison with unmodified polyurethanes. Chattopadhyay et al [39] related lower values of storage modulus with the lower tensile strength of the material. On the other hand, decrease in storage modulus and loss modulus with the increase in the filler amount was correlated interactions of modifier with PUR matrix, which impact on the thermomechanical properties of obtained PURs [37,40].…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 99%
“…The opposite effect of the clay nanofiller on the elongation at break and tensile strength was reported for the PC‐PU‐based organoclay NCs . The elongation at break decreases of about 20% in PC‐PU/BO NCs . Moreover, ZnO NPs loading cause the decrease of the Young's modulus, tensile strength, elongation at break and hardness of the NCs because of poor interfacial interaction between ZnO NPs and PC‐PU matrix .…”
Section: Characterizationmentioning
confidence: 90%
“…Hence, a wide range of nanoadditives with different types and different properties as reinforcement fillers can be incorporated within the APCs to improve the overall characteristics of these polymer matrices. For instance, Špírková et al synthesized the APC‐based polyurethane (PC‐PU), as well as its NCs filled with different kinds of nanoparticles (NPs) such as organic‐modified clay and zinc oxide (ZnO) NPs. They found that these NCs exhibit excellent mechanical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Thus this leads to the additional information of the other thermal events, which remain hidden and cannot be obtained by a normal DSC scans. Therefore, this technique has been extensively used to characterize the thermal properties of polymers [16][17][18][19][20][21][22][23] . The basic limitation of TMDSC experiment lies on the low range frequency (<1 Hz) window for which the thermokinetic parameters at higher frequency cannot be probed.…”
Section: Introductionmentioning
confidence: 99%